2022
DOI: 10.1016/j.jaim.2020.10.008
|View full text |Cite
|
Sign up to set email alerts
|

A prospective clinical study of an Ayurveda regimen in COVID 19 patients

Abstract: Introduction The ancient Indian system of medicine, Ayurveda has a treatment for symptom complexes of a variety of disease. One such combination of Ayurvedic medications has potential for use in COVID 19 infection, hence a prospective study was conducted with this formulation as an add on, in COVID positive patients in a dedicated COVID Hospital. Objective To evaluate the additional benefit of an Ayurvedic regime in COVID +ve patients on the basis of rate of clinical im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 9 publications
1
28
0
Order By: Relevance
“…Ayurveda findings are similar to recently published results of a study demonstrating that the Ayurveda combination appeared to accelerate recovery of patients hospitalized for COVID 19 infection, in terms of reduction of symptoms and duration of hospital stay. 30 Our preliminary results also suggest a similar effect of the combination of Ayurveda to prevent severe respiratory tract infections when administrated to patients suffering from viral infection. Further studies on this combination are needed, since such combination may both act as an antiviral therapy against SARS-CoV-2 and prevent bacterial super-infections.…”
Section: Efficacy Outcomessupporting
confidence: 63%
See 1 more Smart Citation
“…Ayurveda findings are similar to recently published results of a study demonstrating that the Ayurveda combination appeared to accelerate recovery of patients hospitalized for COVID 19 infection, in terms of reduction of symptoms and duration of hospital stay. 30 Our preliminary results also suggest a similar effect of the combination of Ayurveda to prevent severe respiratory tract infections when administrated to patients suffering from viral infection. Further studies on this combination are needed, since such combination may both act as an antiviral therapy against SARS-CoV-2 and prevent bacterial super-infections.…”
Section: Efficacy Outcomessupporting
confidence: 63%
“…Ayurveda findings are similar to recently published results of a study demonstrating that the Ayurveda combination appeared to accelerate recovery of patients hospitalized for COVID 19 infection, in terms of reduction of symptoms and duration of hospital stay. 30…”
Section: Discussionmentioning
confidence: 99%
“…In another docking study 6 gingesulphonic acid which is present in Sunthi (Zingiber officinale Roscoe) showed higher binding energy and inhibition to protein molecule of SARS-CoV-2 compared to hydroxychloroquine and quinine [ 17 ]. In a Prospective clinical study comprising Daśmūlakaṭtrayādi kaṣāya and Guḍūcyādi kvātha tablets as add on to standard care showed a faster recovery from breathlessness with reduced ageusia and accelerate recovery in terms of reduction of symptoms and duration of hospital stay [ 18 ].…”
Section: Potential Role Of Ayurveda and Yoga In Covid-19 Infection: Current Evidence Basementioning
confidence: 99%
“…More recently, there are reports of the use of Ayurveda for prophylaxis as well as treatment of In an open-label randomized controlled trial performed on COVID patients with mild to moderate symptoms in a tertiary care facility [45], the Ayurvedic medicines Dasamoolkaduthrayam Kashaya and Guluchyadi Kwatham (in tablet form) were administered as adjunct to the Standard of Care treatment to the treatment group; the Ayurvedic regime was observed to have fastened recovery in terms of reduction of symptoms (particularly breathlessness) as well as duration of stay in hospital. In another randomized controlled trail [40] that used the Ayurvedic medicine Guduchi Ghan Vati in addition to the standard treatment for asymptomatic COVID patients, all the patients in the intervention group continued to remain asymptomatic while 11.7% of those in the control group developed mild symptoms; moreover, significant differences between the two groups were observed in terms of duration of hospital stay as well as virologic clearance on days 7 and 14.…”
Section: Introductionmentioning
confidence: 99%